The Influence of Microsurgical Training on the Practice of Hand Surgeons - Christensen, Thomas J.; Anding, William; Shin, Alexander Y.; Bishop, Allen T.; Moran, Steven L. (Journal of Reconstructive Microsurgery, 2015)
Background The study aims to determine the effect of formal training on the long-term practice of microsurgery.Methods Hand surgeons completing a 1-year hand fellowship and a 5-day microsurgery rat-model training course from a single institution over a 15-year period (1996–2011) were surveyed. Patency rates (at 24 hours), additional days spent in the laboratory, and training (orthopedic [OS] vs. plastic surgery [PS]) were correlated with the questionnaire responses regarding microsurgical confidence and practice spectrum.Results Data were obtained for 100% (61/61) of former fellows. PSs were 4.7 and 7.6 times more likely to perform replants and free flaps than OSs, respectively. Training patency rates and days in the laboratory were fair predictors of current practice of free flaps and replants.Conclusion PSs are more likely to perform replants and free flaps than OSs. Successful completion of a microsurgical skills course can be used as a predictor of those who will ultimately practice microsurgery. Broader application of microsurgical skills labs may be a technique to increase the practice of microsurgery among all hand surgeons.
Keywords: education; free flap; laboratory training; microsurgery; microsurgical training; replantation